2020
DOI: 10.1111/jfpp.14405
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on Tianjin and Baiyangdian preserved eggs pickled by vacuum technology

Abstract: In this study, the Tianjin and Baiyangdian duck eggs were used to pickle the preserved eggs by a novel technology-vacuum technology. The curing time of vacuum technology was reduced by three times compared with the traditional method. The weight gain rates of preserved eggs pickled by the traditional method first increased and then decreased, while the preserved eggs pickled by vacuum technology were How to cite this article: Sun N, Liu H, Wen Y, et al. Comparative study on Tianjin and Baiyangdian preserved eg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Researchers have created techniques for pickling that are stress free. According to Sun et al ( 3 ), vacuum technology has a three-fold shorter curing time than conventional methods. Strong alkali's effect during pickling causes the proteins in fresh duck eggs to break down into free amino acids and tiny peptides, and the lipids to break down into free fatty acids ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have created techniques for pickling that are stress free. According to Sun et al ( 3 ), vacuum technology has a three-fold shorter curing time than conventional methods. Strong alkali's effect during pickling causes the proteins in fresh duck eggs to break down into free amino acids and tiny peptides, and the lipids to break down into free fatty acids ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, combining the decompression technology with other methods could effectively increase the pickling speed. Some research has shown that the vacuum technology reduces the pickling time of the preserved eggs by about 2/3 ( Sun et al., 2020 ). Vacuum pickling induces rapid changes in preserved egg whites, in which the sulfhydryl group and surface hydrophobicity increase, whereas disulfide bonding reduces.…”
Section: Rapid Pickling Technologies For Pickled Eggsmentioning
confidence: 99%